Estrutura genética e relações de parentesco em populações de colhereiro (Platalea ajaja, Aves: Ciconiiformes) - Miño, Carolina Isabel (2006)
The Roseate Spoonbill (Platalea ajaja, Aves: Threskiornithidae) is a wading bird species which breeds in wetland colonies from the southern United States (US) to the pampas of Argentina. Brazilian colonies are abundant in the Pantanal region, Rio Grande do Sul marshes and in the north region of this country. Adults undergo two annual molt periods which partially overlap with the reproductive cycle. The species has been described as socially monogamous based on field observations of only one couple. We sampled five Pantanal and one Rio Grande do Sul breeding colonies, applying nestling blood and feather sampling and a new non-invasive methodology, the collection of adult molted feathers. Four species-specific and one heterologous microsatellite markers were used to characterize the genetic variability distribution and levels of genetic structure within and between the colonies; to estimate levels of genetic relatedness between nestlings found at the same nest to infer about breeding behavior in the wild; and to estimate and compare the distribution of genetic variability and values of genetic relatedness between male and female adults to infer about patterns of natal dispersal. Mean observed heterozigosity (0,575) was comparable to the reported for a wild-caught population maintained in a US zoo. Results are discussed supposing reduced losses of genetic variability in the US population after the population decline undergone by it, or by a rapid recovery of this population after the bottleneck. Another possibility was hypothesized considering that Brazilian Pantanal population may be declining. No evidences were found of genetic structuring nor differentiation between the colonies (global FST = -0.002, P: 0,59), thus suggesting the existence of high levels of recent or past gene flow between them. Unexpected low relatedness values with significant probability (LOD) values were observed for some dyads found at the same nests. We suggest that extra-pair copulation and/or brood parasitism, already observed in captivity birds, can be occurring in Roseate Spoonbill natural populations, but this fact may be further explored. Comparative analyses showed that genetic variability distribution and relatedness values did not differ significantly between male and female adult samples. The interpretation of these results indicates that both sexes of Roseate Spoonbill apparently present similar patterns of natal dispersal.